Implementasi Algoritme Trivium dan Diffie-Hellman Key Exchange Pada Protokol CoAP - Muhammad Alvian Syahputra; Ari Kusyanti; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Constrained Application Protocol (CoAP) is a communication protocol that was created for devices with constrained resources. Some of its feature are low header overhead and low parsing complexity which make CoAP a good choice for communication protocol in Internet of things (Iot) base system. However, this protocol does not have security feature, the data that was sent by this protocol can easily be seen by a sniffing attack which mean an attacker can easily read any confidential data that was sent by CoAP. One way to solve this problem is encrypting the data before sending it with CoAP so that an attacker cannot read the data. In this study, we build a simple client-server system that use CoAP as its communication protocol and also implement a stream cipher called Trivium with Diffie-Hellman key exchange (DHKE) to secure the data. The results from this study show that attacker can get the ciphertext only from doing a sniffing attack on the system and not the actual data. The system takes an average of 0.055414 second to encrypt data, an average of 0.058667 second to decypt the ciphertext, and an average of 1.741022 second to send a data which include doing handshaking proses, encrypting data and decrypting the ciphertext. Even though the system is capable to maintain data confidentiality, it still very vulnerable from attacks such as Active Man-in-the-Middle and Crib Dragging.